Nursing Education in a Real-Life Context: The Teaching Ward Round - Juan Miguel Martínez-Galiano; Laura Parra-Anguita; Miguel Delgado-Rodríguez; Manuel González-Cabrera (MDPI AG, 2021)
Education in nursing is continually changing. The didactic methods used in other fields may be useful for closing the gap between theoretical learning and the reality of practical nursing. This study aimed to determine the association between a teaching model centered on the reality of nursing care, which is individualized to each context, and knowledge acquisition. A controlled experimental study was conducted with random allocation to two groups of students in their second year of a nursing degree (University of Jaén). The control group undertook practical work placements according to the traditional model. The intervention group participated in a "teaching round" during their practical placements. Knowledge tests were conducted after the placements. No significant differences were found for age or education level between the students of the control group (n = 46) and the intervention group (n = 48). In terms of the association between participation in the teaching round and the knowledge test (maximum score of 10), the mean grade in the intervention group was 8.83 ± 0.22, while it was 7.68 ± 0.23 in the control group (p = 0.001). The teaching round increased the student's acquisition of knowledge, even though this was not reflected in the global grade of the course.